PENDAPATAN DAN MANFAAT USAHATANI PADI ORGANIK DI KABUPATEN PRINGSEWU - Ari Nurjayanti; Irwan Effendi; Indah Nurmayasari (Lampung University, 2016)
Pesticide and chemical fertilizer usage in rice farming is known to deteriorate soil and environment. Organic rice farming is developed. However, there are not many farmers who cultivate organic compared to nonorganic rice. The objectives of this research are to analyze the cost, production, the income of organic and nonorganic rice farming, and to explore the benefits of organic rice farming. This research was conducted in Pringsewu Regency in August 2015. The sampling method employed was a census on 30 farmers cultivating organic rice in two villages, and simple random of 30 farmers cultivating nonorganic rice. Data were analyzed using farming analysis and descriptive qualitative. The results showed that organic rice production (6,587 kg per ha) was lower than nonorganic rice production (6,630 kg per ha in two planting seasons). The production cost of organic rice farming was higher (Rp39,011,679.00 per ha) than that of nonorganic rice farming (Rp30,326,937.00 per ha in two planting seasons). Income of organic rice farming was higher than nonorganic, Rp50,759,725.00 and Rp24,454,808.00 respectively. Organic rice farming was more profitable than nonorganic rice farming with the R/C on the total cost of organic rice farming of 2.30 and nonorganic rice farming of 1.81. The B/C was 3.03. In addition to economic benefit, farmers of organic rice obtained social benefits such as providing job field and farmer groups’ activity. Environmental benefits that were obtained by farmer were reducing dependence on chemicals and creating a secure work environment for farmers. Key words: benefit, organic rice, production, profit